Penguatan Literasi Membaca Teks Prosedur K3LH melalui Media Digital pada Murid SMK: Strengthening Reading Literacy of K3LH Procedure Texts through Digital Media for Vocational High School Students - Kristiani Nainggolan; Esti Swastika Sari; Ary Kristiyani (ITScience (Information Technology and Science), 2026)
The low reading literacy skills of Vocational High School (SMK) students, especially their understanding of procedural texts related to Occupational Safety, Health, and the Environment (K3LH), pose a challenge for vocational-based Indonesian language learning. This condition results in less-than-optimal student understanding of work procedures relevant to the needs of the industrial world. This study aims to improve reading literacy skills with K3LH-based procedural texts through interactive digital media. The study used the Classroom Action Research (CAR) method with the Kemmis and McTaggart model, which includes the stages of planning, action, observation, and reflection. The research subjects consisted of 71 grade XI students from the Heavy Equipment Engineering, Mining Geology Engineering, and Oil and Gas Production Engineering expertise programs at SMK Negeri 1 Bunyu. The study was conducted in two cycles, using data collection techniques including reading literacy tests, observations, questionnaires, and documentation. Data were analyzed using quantitative and qualitative approaches. The results showed that the use of interactive digital media significantly improved students' reading literacy skills. The average student score increased from 68 in cycle I to 82 in cycle II, while learning completion increased from 45% to 82%. Furthermore, students demonstrated improved abilities in understanding the structure of procedural texts, identifying key information, understanding technical terms related to occupational health and safety (K3LH), and relating the text content to their respective fields of expertise. Student activity and engagement during learning also increased. These findings indicate that interactive digital media is effectively used as a contextual, engaging, and relevant learning strategy to strengthen reading literacy while increasing K3LH awareness in vocational education.